Kurangnya efektivitas undang-undang tipikor dalam menjerat kasus korupsi pejabat di indonesia - Arif, Muhammad Farhan (Maliki Interdisciplinary Journal, 2025)
Corruption in Indonesia is a long-standing structural phenomenon that has hampered clean governance and sustainable national development. Although Indonesia has a relatively strong legal framework, Law No. 31 of 1999 concerning the Eradication of Corruption, which was later amended by Law No. 20 of 2001, the reality on the ground shows that this regulation is still ineffective in imprisoning corruption cases involving public officials, both at the regional and local levels. This ineffectiveness is not only evident in the legal aspect but also in the substitution of laws, the legal culture of society, and weak coordination between law enforcement agencies. This research is motivated by the high level of corruption among officials, especially members of the Regional People’s Representative Council (DPRD) and ministerial/institutional officials, despite the existence of severe criminal penalties in the law. This research is motivated by the high level of corruption among officials, especially members of the Regional People’s Representative Council (DPRD) and officials of ministries/institutions, despite the existence of severe criminal threats in the law. In line with data from the Corruption Eradication Commission (KPK) and Indonesia Corruption Watch (ICW), every year there are still dozens of public officials caught in large-scale corruption operations. These results indicate that the ineffectiveness of the anti-corruption law in punishing public officials is caused by several factors, namely the existence of legal loopholes such as in abuse of authority and proof of gratification cases that are often difficult to prove formally. Weakening politics in Indonesia, namely that the legislative process and law enforcement practices remain influenced by certain political interests, so it is not uncommon for officials in strategic locations to enjoy unofficial protection from political networks and the inconsistency of law enforcement officials in implementing regulations. Although the KPK is relatively independent in enforcing the law, there are limited authority and difficulties in coordinating with other institutions such as the police and the prosecutor’s office.